Appraisal of the Parameters of the Lithoprobe Abitibi-Grenville Seismic Reflection Survey - Barnes, Arthur; Bellefleur, Gilles; Ludden, John; Milkereit, Bernd (Geoscience Canada, 1994)
Summary The 1990-1991 Lithoprobe Abitibi-Grenville seismic reflection survey comprises 989 km of regional data collected forcrustal exploration and 81 km of high-resolution data collected for mineral exploration. A proper interpretation of thedata requires an understanding of its limitations; these are a function of the acquisition parameters. The vertical resolution is -38 m for the regional data and 15 m for the high-resolution data. The maximum reflector dip that can be imaged in shallow data is ~70°, but deep data are biased toward subhorizontal reflections. The principal sources of noise are vibrator truck noise, groundroll, and shear wave refractions. Power-line noise is surprisingly important onsome high-resolution lines. The seismic signal penetrates to the Moho, revealing differences in Moho reflectivity across the survey.